G167(P) A case series of human parechovirus associated sepsis and meningitis in young children. (May 2019) - Urooj, F; Flinders, P; Paul, J; Padmakumar, B
Abstract : Introduction: Human Parechovirus (HPeV) and Enteroviruses are frequent cause of sepsis and meningitis in neonates and young children. Background: HPeVs are RNA viruses with similar characteristics to enteroviruses. They are usually associated with mild respiratory or gastrointestinal symptoms. HPeV genotype 3 (HPeV3) is exceptional because it can cause sepsis and meningoencephalitis leaving neurological sequelae and sometimes death in young infants. However, although it is well established, it is not readily recognised by all paediatricians. Case description: We present four patients, two male and two female, aged 1–10 weeks old admitted to children's ward. All subjects presented with high grade fever, sepsis-like-picture and excessive irritability suggestive of central nervous system (CNS) involvement. All were born at term with no significant birth history or previous medical history. On examination, two of them were noted to have a maculo-papular rash. All children received intravenous ceftriaxone and aciclovir. Laboratory results: Three CSF samples had a mean white cell count of 2.6 (range 0–5) with a predominance of lymphocytes. The fourth sample was heavily blood stained so white cell count was inconclusive. Mean serum CRP value was 5.8 mg/L (range 2.5–11.7 mg/L). No organisms were revealed on gram stain and microbiology cultures did not yield any growth. HPeV was detected by reverse transcription polymerase chain reaction (RT-PCR) in three CSF samples. For the fourth sample, CSF volume was insufficient however blood was tested and was HPeV positive by PCR. Conclusion: HPeV is a recognised cause of neonatal sepsis and CNS involvement in young children. In our cases, two were neonates and two were aged between one and three months of age. This case series demonstrates that HPeV should be suspected and included in the work up of both neonates and young children (<3 months old), presenting with sepsis or meningitis. Enterovirus is a well-recognised cause of viral meningitis and neonatal sepsis. We have demonstrated four cases of HPeV that clinically mimicked enterovirus infections. All young children presenting with sepsis or meningitis should be tested for HPeV along with enteroviruses.